Organizational Culture, Motivation and Organizational Citizenship Behavior Effect on Employee Performance - Syahrul Nur Rizky; Hadi Sunaryo; Agus Salim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Employees are human resources who play an important role in achieving organizational goals, employees who excel and have high work quality certainly bring benefits and organizational progress. Organizational culture, motivation and organizational citizenship behavior are a concern for organizations in providing encouragement to employees to carry out activities in the organization. Organizational culture as a value, belief and boundaries accepted by employees in determining the extent to which they act. Organizational culture has a role in improving performance, so motivation is the driving force or impetus that causes employees to take an action to achieve goals. Improving employee performance cannot be separated from individual roles such as organizational citizenship behavior which involves several behaviors, including helping others, volunteering for extra tasks, obeying workplace rules and procedures. This research was conducted on employees of the Kebonagung Sugar Factory in Malang with a sample of 50 employees. Data collection methods using questionnaires. The analysis used includes instrument testing, classical assumption test, normality test, multiple linear regression, hypothesis testing and coefficient of determination test using multiple regression analysis with the help of SPSS 14.0 software for Windows. The results showed that organizational culture and motivation had no significant effect on employee performance, while organizational citizenship behavior had a significant effect on employee performance.